PROTOTIPE SISTEM MONITORING DAN PENGGANTIAN OTOMATIS INTRAVENOUS FLUID DROPS - Awlan Suryandaru, Afrizal; Putra Sastra, Nyoman; Diafari Djuni, Gst A Komang (Jurnal SPEKTRUM, 2021)
The giving of intravenous fluids to patients is dispense fluids into the veins using an infusion set with a certain amount and period. Patients who are given intravenous fluids will constantly be monitored by a nurse manually and regularly. In this study, a monitoring system and automatic replacement of intravenous fluids drops were designed to make it easier for nurses to monitor and change infusions automatically. The monitoring system is designed to take advantage of the Telegram communication application integrated with the NodeMCU ESP8266. In contrast, the automatic replacement system utilizes an infrared sensor to detect fluid availability. Based on the research results, the infrared sensor will have a logic '1' if infusion fluid is more than 50ml, and the sensor will have a logic '0' if infusion fluid is less than 50ml. The fastest system response to send sensor data to Telegram Bot reached 01.10 seconds, while the fastest system response to receive orders from Telegram Bot reached 05.70 seconds.